Water polo shots notational analysis according to player positions - Ozkol, M. Z.; Turunc, S.; Dopsaj, M. (International Journal of Performance Analysis in Sport, 2013)
The objective of this study was to examine the offense positions a shot is taken in the field and the ending points of the shots taken from a spot of equal number of defense and offense players (6-6). Matches were recorded (14 match) by a camera and recordings were analyzed by marking and collecting data with notation match analysis method. Repeated measures of ANOVA was used for the statistical analysis. Significant differences were found in 4 of the 6 positions (p3, p4, p5, p6) in shot efficiency (p0.05). The highest shot efficiency was in P6 (65.35%) and at the overhead (52.52%) in goal. Significant differences were found in 4 of the 6 positions (p1, p3, p5, p6) in goal efficiency